PEMBERDAYAAN MASYARAKAT MELALUI ”ENGLISH VOWELS” DI RRI SURAKARTA - Widyashanti Kunthara Anindita; Ika Oktaria Cahyaningrum; Ramadan Budiman; Titis Ary Laksanti (Batara Wisnu : Indonesian Journal of Community Services, 2023)
This community service activity was carried out at RRI Surakarta under the direct guidance of DPL and English Literature S1 Students from Surakarta University. The material presented is from the book entitled "English Phonetics and Phonology" written by Peter Roach (1998). The material elements presented include vowels (long and short vowels), dipthong and monophthong. The target audience is the wider community who listen to this program at RRI Surakarta. Service is carried out in three activities, namely; lecturing, listening to cassettes, pronunciation practice (response from the listeners or RRI Surakarta officers). All activities ran smoothly because of extra help/demonstrations from the lecturers. The aims of this service are to introduce and practice the pronunciation of English vowels with the help of symbols in the dictionary, and to be able to compare the pronunciation of English vowels with Indonesian or Javanese which they are more proficient in. It is hoped that this service will be useful in encouraging community interest, especially in the Surakarta area, to learn independently without always being in class with the help of a teacher. In this way, it is hoped that the English of Surkarta people will be better and more communicative. Evaluation during the service showed a positive response from the participants